2020
DOI: 10.1108/jfbm-10-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

When is the right time for succession? Multiple cases of family businesses in Indonesia

Abstract: PurposeSuccession timing plays a key role in the part of the succession process. While much notice has been given solely to the viewpoint of predecessor and successor, less known about the schedule during this most critical family business dealings. The purpose of this research is to assess the right time for predecessors to let go of their leadership and allow the successor to take charge of the family business. Notably, it considers how the process of interaction between predecessor and successor may encoura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Istiatin and Luhgiato (2017) announced three keys to achieving third-generation success in leading a family business: the successor characteristics, transformation, and family harmony. Meanwhile, Tirdasari and Dhewanto (2020) report that the right time for business succession is when the predecessor is within the ages of 41-50 and the successor is within ages 19-25. Regarding gender, it has been reported that Chinese family businesses still maintain a Confucian culture (Anggadwita et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Istiatin and Luhgiato (2017) announced three keys to achieving third-generation success in leading a family business: the successor characteristics, transformation, and family harmony. Meanwhile, Tirdasari and Dhewanto (2020) report that the right time for business succession is when the predecessor is within the ages of 41-50 and the successor is within ages 19-25. Regarding gender, it has been reported that Chinese family businesses still maintain a Confucian culture (Anggadwita et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mereka mungkin berfungsi sebagai keluarga pemilik, anggota dewan, manajer atau pekerja, sebagai serta orang tua di rumah. Masing-masing partai punya persyaratan keterampilan unik dan kebutuhan belajar (Tobak & Nábrádi, 2020;Tirdasari & Dhewanto, 2020). Ketiga, dimana anggota keluarga yang sama bekerja bersama-sama, mereka mungkin mengalami emosi yang kuat dari cinta berbakti dan altruisme orang tua, hingga pribadi permusuhan yang berasal dari persaingan saudara awal.…”
Section: Pendahuluanunclassified
“…Observation and strategic planning are factors that can influence succession in family businesses. Observation can help the next generation understand and appreciate the values and business practices implemented by the previous generation (Tirdasari & Dhewanto, 2020). Through observation, the next generation can identify the challenges and business opportunities faced by the family business and develop the skills and knowledge needed to manage the business successfully.…”
Section: "I Joined Work With My Parents Initially Because I Felt Like...mentioning
confidence: 99%